Cord blood 25-hydroxyvitamin D3 and allergic disease during infancy - Jones, A.; Palmer, D.; Zhang, Guicheng; Prescott, S. (2012)
OBJECTIVE: There has been growing interest in vitamin D insufficiency as a predisposing factor for allergy development based on immunoregulatory properties and epidemiological studies. The aim of this study was to investigate the association between vitamin D exposure in utero and allergic outcomes in the first year of life. METHODS: Cord blood (CB) vitamin D was measured in 231 high-risk infants froman Australian prospective birth cohort. CB 25-hydroxyvitamin D3 (25[OH]D3) concentration was analyzed in relation to maternal vitamin D intake and the development of infant eczema, allergen sensitization, and immunoglobulin E-mediated food allergy. RESULTS: Maternal intake of supplemental vitamin D was significantly correlated with CB 25(OH)D3 concentration (r = 0.244, P = .003), whereas dietary vitamin D did not influence CB levels. There was significant seasonal variation in CB 25(OH)D3 concentration suggesting that sunlight exposure was an important determinant. Lower CB vitamin D status was observed in infants that developed eczema (P = .018), and eczema was significantly more likely in those with concentrations <50 nmol/L in comparison with those with concentrations =75 nmol/L (odds ratio 2.66; 95% confidence interval 1.24-5.72; P = .012). This association remained significant after adjustment for multiple confounding factors. The associations between CB 25(OH)D3 concentration and allergen sensitization, immunoglobulin E-mediated food allergy, and eczema severity (SCORing Atopic Dermatitis) were not significant. CONCLUSIONS: Reduced vitamin D status in pregnancy may be a risk factor for the development of eczema in the fi rst year of life, reinforcing the need to explore the role of vitamin D exposure during development for disease prevention. Copyright © 2012 by the American Academy of Pediatrics.